Embolism spread in the primary xylem of Polystichum munitum: implications for water transport during seasonal drought. (14th November 2015) - Brodersen, Craig R.; Rico, Christopher; Guenni, Orlando; Pittermann, Jarmila
Abstract: Xylem network structure and function have been characterized for many woody plants, but less is known about fern xylem, particularly in species endemic to climates where water is a limiting resource for months at a time. We characterized seasonal variability in soil moisture and frond water status in a common perennial fern in the redwood understory of a costal California, and then investigated the consequences of drought‐induced embolism on vascular function. Seasonal variability in air temperature and soil water content was minimal, and frond water potential declined slowly over the observational period. Our data show that Polystichum munitum was protected from significant drought‐induced hydraulic dysfunction during this growing season because of a combination of cavitation resistant conduits (Air‐seeding threshold (ASP) = −1.53 MPa; xylem pressure inducing 50% loss of hydraulic conductivity ( P50 ) = −3.02 MPa) and a soil with low moisture variability. High resolution micro‐computed tomography (MicroCT) imaging revealed patterns of embolism formation in vivo for the first time in ferns providing insight into the functional status of the xylem network under drought conditions. Together with stomatal conductance measurements, these data suggest that P . munitum is adapted to tolerate drier conditions than what was observed during the growing season. Abstract : Xylem network structure and function have been characterized for many woody plants, but less is known about fern xylem. We characterized seasonal variability in soil moisture and frond water status in a common perennial fern ( Polystichum munitum ) in the redwood understory of costal California, and then investigated the consequences of drought‐induced embolism on vascular function and gas exchange. Overall, this species was surprisingly resistant to long‐term drought and maintained water transport capacity. Using high resolution X‐ray computed tomography we visualized for the first time the spatial pattern of embolism formation in a fern. The xylem network organization utilized by this species provides a spatially discrete water transport system that limits the systemic spread of embolism, and this strategy is one of several adaptations P . munitum uses to survive long periods with infrequent precipitation.